The Effectiveness of Academic Supervision of Principal in Improving Distance Learning in Junior High School - Ellyta Ellyta; Murniati Murniati; Nasir Usman (STAI Hubbulwathan Duri, 2022)
Academic supervision is a process taken by the principal to assist teachers in increasing their ability to manage the effective learning. This study aims to determine the program, implementation, role of supervisors, supporting and inhibiting factors for the principal's academic supervision in improving online learning during the covid-19 period at SMPN 19 in Banda Aceh. The data collection techniques used were observation, interview, and documentation study. The research subjects were school principals and teachers. The data analysis used was reduction techniques, data presentation, data interpretation and data verification. The results showed that: the effectiveness of the implementation of academic supervision of school principals in the Covid-19 pandemic at SMPN 19 Percontohan in Banda Aceh was seen from : (1) The planning for the academic supervision of school principal is conducted by cooperating with all education stakeholders in providing quality education as determined by all parties, including teachers and school principal. (2) The implementation of the academic supervision of the principal is conducted by seeing the teacher perform the distance learning and offline learning through lesson planning which includes competency standards, basic competencies, indicators of success, and teaching materials, the presentation of fun material, the use of appropriate methods, the existence of media to support the learning process and assignments that are able to measure all student abilities. (3) The principal provides guidance, direction, and guidance to teachers who still have weaknesses and deficiencies in managing learning; (4) The supporting factors for academic supervision are the high of teacher awareness, good teacher perceptions of academic supervision, and motivation / support from parents to students.